The purpose of intervention changing beliefs about the use of force - Finnemore, Martha (Ithaca Cornell University Press, 2003)
Violence or the potential for violence is a fact of human existence. Many societies, including our own, reward martial success or skill at arms. The ways in which members of a particular society use force reveal a great deal about the nature of authority within the group and about its members' priorities.
Includes bibliographical references and index.
Keywords: Intervention (International law)